EFISIENSI PEMASARAN UBI JALAR DIKECAMATAN SIDOREJO, KABUPATEN MAGETAN - Istiqomah, Istiqomah; Hasan, Fuad; Wijayanti, Dian Eswin (Universitas Trunojoyo Madura, 2025)
This study aims to identify marketing institutions and channels along with their functions, analyze marketing margins, farmer’s share, and sweet potato marketing efficiency in Sidorejo District, Magetan Regency. Data were collected using structured interviews with farmers and marketing institutions. Data were analyzed descriptively quantitatively. The results show that the marketing institutions involved in sweet potato distribution in Sidorejo District consist of middlemen, collectors, and retailers, with the dominant role held by middlemen and retailers. The marketing channels are formed into four channels, and each marketing institution carries out marketing functions that include transportation, packaging, and storage. Some channels show high marketing efficiency values mathematically, but the farmer’s share received by farmers remains low, this indicates an imbalance in the distribution of profits between marketing actors